Sexual Politics: Mapping the Body in Marguerite Duras’s L’Amant - Gray II, Richard J. (Romanica Silesiana)
<!--EndFragment-->In L’Amant (1984), through the juxtaposition of traditional male/female sexual roles, Marguerite Duras painted a gynocentric portrait of sexual politics. By depicting a series of encounters in diverse parts of the Indochinese (Vietnam) landscape, Duras’s novel described the sexual “coming of age” story of her female protagonist’s. Each Vietnamese setting became a visual and sensory metaphor for the various developmental stages of the protagonist. In this essay, I contend that Duras’s use of contrasting settings serves to “flesh out” the sexual politics conveyed in the novel. Herein, I examine the geographic locations illustrating the sexual politics of the novel, including the Mekong River signifying the female protagonist’s rite of passage, Cholon, the city where the girl experiences sexual liberation and a struggle with the established authority, the lover’s apartment where the couple consummates their relationship, and finally, France representing the land of wealth to which the protagonist will eventually return. Key words: autobiography, Judith Butler, Cholen (Cholon), colonisation, crossing, gender, juxtaposition, Marguerite Duras, Julia Kristeva, liberation, liminal space, mapping the body, Mekong, Kate Millett, Other, post-colonial, prostitution, sexploitation, sexuality, sexual politics.